2016
DOI: 10.1186/s40604-016-0034-9
|View full text |Cite
|
Sign up to set email alerts
|

Hidden mediator roles of university spin-offs in Triple Helix networks

Abstract: University spin-off firms contribute to bringing knowledge created at university to market. The networks these firms employ with other Triple Helix actors serve as not only getting access to resources but also shaping processes of collective learning in transforming the knowledge most adequately. In addition, spin-offs may affect the networks and behavior of network participants. While the first role has received large attention, collective learning and transforming networks and network partners have not. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Additional research is thus suggested in this Patenting Activity area, not only related to the aforementioned factors but connected also to the knowledge and financing necessary to successfully patent new products -the external environment, namely economic crises such as the one in Portugal at the time of writing -are expected to negatively affect patenting activity as the necessary funds will be more difficult to come by. This has been confirmed by previous research into university spin-off activity, involving Portugal, Poland, Finland and the Netherlands -where gaining financial capital was an important barrier to overcome, on the path to university spin-off growth (Oliveira et al 2013;Van Geenhuizen and Ye 2012). Furthermore, Moutinho et al (2007) survey of scientists' patenting in Portuguese public research organizations revealed that the majority "believed that there are many difficulties associated with the patenting process and that they receive limited support from their organizations, which lack the proper competences and structures to assist with patenting and licensing" (Moutinho et al 2007, p. 355).…”
Section: Discussionsupporting
confidence: 84%
“…Additional research is thus suggested in this Patenting Activity area, not only related to the aforementioned factors but connected also to the knowledge and financing necessary to successfully patent new products -the external environment, namely economic crises such as the one in Portugal at the time of writing -are expected to negatively affect patenting activity as the necessary funds will be more difficult to come by. This has been confirmed by previous research into university spin-off activity, involving Portugal, Poland, Finland and the Netherlands -where gaining financial capital was an important barrier to overcome, on the path to university spin-off growth (Oliveira et al 2013;Van Geenhuizen and Ye 2012). Furthermore, Moutinho et al (2007) survey of scientists' patenting in Portuguese public research organizations revealed that the majority "believed that there are many difficulties associated with the patenting process and that they receive limited support from their organizations, which lack the proper competences and structures to assist with patenting and licensing" (Moutinho et al 2007, p. 355).…”
Section: Discussionsupporting
confidence: 84%
“…Likewise, the Research Leader 'regarded the [Spin-Off Company] as an entirely private matter, with no ties to the university other than the temporary rental of laboratory space' (Tuunainen 2004: 56). Thus, notwithstanding (or, perhaps, because of) their relationship conflicts (Ranga and Etzkowitz 2013;van Geenhuizen et al 2016), all parties seemed to have agreed, while still acting only upon their respective divergent personal and institutionalised agendas and never in the overall interest of the common, that the Hybrid Firm either was or should be considered non-existent. As a result, and with no more than 2 years in operation (Tuunainen 2002: 50), the Hybrid Firm-the very 'locus of innovation' (Todeva 2013: 273; see also Boon et al 2011: 250)-was deliberately dissolved and 'de-hybridised.'…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Similarly, Metcalfe (2010: 504) has found the fully-integrated trilateral networks of the triple helix to be 'understudied, ' prompting her to critically explore and model 'the role of external organizations in the formation of AIG ties.' Notwithstanding the relatively small sample of directly applicable scholarship, more developed literatures tackling intermediation and intermediary organisation exist within many disciplines (Landry et al 2013;Todeva 2013)-in particular, for current purposes, in the related research fields of innovation and technology transfer intermediation (Boon et al 2011;Dalziel 2010;Dalziel and Parjanen 2012;Gassmann et al 2011;Håkanson et al 2011;Hoppe and Ozdenoren 2005;Howells 2006;Kivimaa 2014;Klerkx and Leeuwis 2008;Kodama 2008;Lichtenthaler and Ernst 2008;Pollard 2006;Sieg et al 2010;Shohet and Prevezer 1996;Stewart and Hyysalo 2008;Suvinen et al 2010;van der Meulen et al 2005;van Lente et al 2003;Villani et al 2016) and knowledge intermediation (Cantù et al 2015;Parker and Hine 2014;Schlierf and Meyer 2013;Wright et al 2008;Yusuf 2008). Even here, however, authors have pointed out that '[d]espite their obvious presence, … innovation intermediaries have received little attention in the theoretical intermediation literature' (Hoppe and Ozdenoren 2005: 484) so that 'relatively few systematic analyses of their functions' (Suvinen et al 2010(Suvinen et al : 1366 are available today (see also van der Meulen et al (2005: 2)).…”
Section: Triple Helix Intermediation and Legal Organisationmentioning
confidence: 99%
See 1 more Smart Citation
“…2) Interacting with each other, such as the cooperation between the university and the industry or the government's policy planning and guidance to industries. 3) The tripartite overlapping of functions formed by the hybrid organization; the three interact and jointly promote the spiral of innovation (Etzkowitz, 2002;van Geenhuizen et al, 2016).…”
Section: The Connotation Of Giu Cooperative Innovation Networkmentioning
confidence: 99%